Construction of personal identity for outside Baduy Citizens on instagram - Amrullah, Haekal Fajri; Bate, Andi Pajolloi; Prasetyo, Kurniawan; Mahmudi, Marwan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social media serves as a means for users to place themselves in the desired framework. Through social media, people can quickly build relationships, add insight, shape, express, and display their identity. Discussions about self-identity become unique and exciting when a Baduy citizen uses social media and forms his identity. Of course, we already know that the Baduy are one of the tribes in the Banten region and are a group of indigenous peoples in the interior who still adhere to the culture of their ancestors. The purpose of this study is to examine how outside Baduy residents construct their identities on Instagram social media. This research uses a qualitative approach with a case study method. The study results show that outside Baduy residents are familiar with gadgets and Instagram social media. The motive for using social media is to promote Baduy products and culture. Instagram makes it easy to access information. The construction of self-identity on Instagram is shown by posting pictures of Baduy characteristics or identities, such as the Instagram account name added with the word "Baduy", Baduy clothes and accessories, daily activities in Kanekes Village, and original Baduy products and customs.